Modern Approach to Miscarriage of Pregnancy - Abdurasulovna, Kamilova Iroda; Shuxratovna, Sharipova Dildora (International Journal on Integrated Education, 2023)
This review article is devoted to the problem of miscarriage, premature birth, developmental etiopathogenesis and modern approaches to the management and treatment of this pathology.